Breast milk vs. non-nutritive sucking to reduce pain from minor invasive procedures in neonates - Sevina Marisya; Guslihan Dasa Tjipta; Supriatmo Supriatmo; Emil Azlin (Indonesian Pediatric Society, 2013)
Background Neonates undergo many uncomfortable, invasiveminor procedures during their first hospital stay. Nonpharmacologicalinterventions may provide valuable alternativesfor pain relief in neonates during minor procedures.Objective To compare the analgesic effect of orally administeredbreast milk vs. non-nutritive sucking (NNS) in neonates whounderwent minor invasive procedures.Methods A randomized, open trial was performed at the Haji AdamMalik Hospital from September to December 2009. Subjects were 96healthy, term infants who received injections of either intramuscularhepatitis B immunization or vitamin K. Subjects were randomlyallocated into two groups, those were the breast milk group (n = 48)and the NNS group (n= 48). Breast milk and NNS were given twominutes before the injection. The events were recorded by videorecorder. Transcutaneous heart rate, oxygen saturation and cryingtimes were recorded. Two observers used the premature infant painprofile (PIPP) scale to evaluate all subjects.Result.s In the breast milk group, there was significant reduction inmeanPIPPscore (P= 0.001) and mean crying time (P= 0.03) comparedto the NNS group. There were no significant differences in mean PIPPscore and crying times between males and females (P= 0.4 and P=0.5,respectively). However, there was a significantly lower mean PIPP scorefor vitamin K injection than for hepatitis B immunization (P=0.002),although mean crying times were not significantly different (P= 0.06).We observed significantly less Oz desaturation at 150 seconds postinjectionin the breast milk group compared to that of the NNS group.However, there was no significant difference in heart rate between thetwo groups throughout the observation period.Conclusion Breast milk administered before an invasive minorprocedure effectively reduces pain in neonates. Breast milkadministered to neonates prior to injection has reduced mean PIPPscores, crying times, and Oz desaturation, compared to neonateswho received NNS in the form of pacifiers.